Investigation of the growth mechanism of SrRuO3 thin films fabricated by pulsed laser deposition. (14th April 2015) - Meng, Jianwei; Chen, Zhihui; Jiang, Anquan
Abstract: SrRuO3 thin films were prepared on (100) SrTiO3 substrates by pulsed laser deposition (PLD), and the dependences of film morphology and growth mode on the defocusing distance, repetition, oxygen pressure and substrate temperature were systematically investigated. Our results suggest that the growth mode transforms from three-dimensional (3D) island formation to two-dimensional (2D) layered growth as the defocusing distance increases. Under high laser repetition, adatoms do not have enough time to diffuse to step edges to promote step advancement; consequently, adatoms aggregate to form islands. The effective diffusivity was estimated as D * = 5 × 10 4 nm 2 /s, which represents the average diffusion including adatoms and small clusters. Decreasing oxygen pressure leads to a change in growth mode from 2D layered to 3D island formation. The X-ray diffraction (XRD) patterns show that under low oxygen pressure, the (00 l ) peaks disappear when l is odd, indicating that oxygen vacancies are preferentially produced in the SrO plane. With decreasing substrate temperature, the growth mode changes from step flow to multilayered growth. The relationship between step width and substrate temperature was investigated, and an activation energy of E a = 0.8 eV was obtained by fitting.